Classification of Shot Selection by Batsman in Cricket Matches Using Deep Neural Network - Khan, Afsana; Nabila, Fariha Haque; Mohiuddin, Masud; Mollah, Mahadi (Brac University, 2022)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2022.